2018
DOI: 10.1159/000494293
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients with Small Intestine Neuroendocrine Tumors

Abstract: Background: The prevalence of small intestine neuroendocrine tumors (SI-NETs) is increasing. Disease progression is often slow and treatment options and long-term survival rates have improved, but little is known about health-related quality of life (HRQoL) in these patients. Objective: To assess HRQoL and its predictors in SI-NET patients receiving contemporary treatments. Methods: We measured HRQoL with 15D and SF-36 questionnaires in 134 SI-NET patients and compared the 15D results to those of an age- and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Quality of life is an important measure of patients' perception of the burden of the disease and the impact of the different treatment modalities. Several studies have reported a worse HRQoL in GEP-NET patients compared to matched controls [80,81]. Particularly, NET patients reported poorer physical function, sleep disorders, discomfort, and depression.…”
Section: Impact Of Quality Of Lifementioning
confidence: 98%
“…Quality of life is an important measure of patients' perception of the burden of the disease and the impact of the different treatment modalities. Several studies have reported a worse HRQoL in GEP-NET patients compared to matched controls [80,81]. Particularly, NET patients reported poorer physical function, sleep disorders, discomfort, and depression.…”
Section: Impact Of Quality Of Lifementioning
confidence: 98%
“…Regional lymphadenopathy is associated with desmoplasia of the mesentery forming a mesenteric mass . Mesenteric desmoplasia/mass causes abdominal pain and small bowel obstruction due to the kinking of the small bowel and mesenteric ischemia, which severely impairs the quality of life . Resection of the primary tumor, regional lymph nodes, and the mesenteric mass is recommended to manage such symptoms and for the possible prognostic benefit even in the setting of unresectable distant metastases .…”
Section: Introductionmentioning
confidence: 99%
“…8,11 Mesenteric desmoplasia/ mass causes abdominal pain and small bowel obstruction due to the kinking of the small bowel and mesenteric ischemia, which severely impairs the quality of life. 12,13 Resection of the primary tumor, regional lymph nodes, and the mesenteric mass is recommended to manage such symptoms and for the possible prognostic benefit even in the setting of unresectable distant metastases. 11,[14][15][16][17][18][19] The latest American Joint Committee on Cancer (AJCC) TNM staging for NETs of the jejunum and ileum (8th edition) defined a new category of N2 as a large mesenteric mass (LMM) >2 cm, 12 or more positive nodes, or involving the main superior mesenteric vessels.…”
mentioning
confidence: 99%
“…Larsson et al[ 25 ] reported mean baseline HADS anxiety and depression scores of 4.6 (SD: 4.0) and 3.2 (SD: 2.7), respectively. Four studies applied the Short Form-36 (SF-36) questionnaire[ 9 , 46 - 48 ], three of which were cross-sectional studies. Other measures used include the SF-12[ 49 ], the Functional Assessment of Cancer Therapy-Anaemia[ 50 ] and the Functional Assessment of Chronic Illness Therapy-Diarrhoea (FACIT-D).…”
Section: Resultsmentioning
confidence: 99%